2011
DOI: 10.1007/s12185-011-0849-0
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node-based disease and HHV-8/KSHV infection in HIV seronegative patients: report of three new cases of a heterogeneous group of diseases

Abstract: We describe three cases of lymph proliferative diseases characterized by the presence of lymphoma cells expressing the KSHV/HHV-8 antigen with or without EBV expression. The patients were HIV seronegative without serous effusions. One case was diagnosed as KSHV-germinotropic lymphoproliferative disorder due to the presence of atypical plasmablasts involving germinal centers. These plasmablasts were positive for MUM1 and vIL6, co-expressed EBV and LNA-1 of HHV-8/KSHV, and showed a polyclonal pattern of Ig gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 21 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…Now, there is a controversy around the participation of HHV-8 in NHL. In this sense, some authors have also agreed that HHV-8 DNA detection in the lymph node would be considered not only as opportunistic infection but also as an agent involved in malignant lymphoproliferation [25]. Furthermore, rare HHV-8 positive solid lymphomas have been described as extra-cavitary PELs forms [26] and Engels and colleagues have previously reported a similar case of NHL from Ugandan pediatric patient [27].…”
Section: Discussionmentioning
confidence: 99%
“…Now, there is a controversy around the participation of HHV-8 in NHL. In this sense, some authors have also agreed that HHV-8 DNA detection in the lymph node would be considered not only as opportunistic infection but also as an agent involved in malignant lymphoproliferation [25]. Furthermore, rare HHV-8 positive solid lymphomas have been described as extra-cavitary PELs forms [26] and Engels and colleagues have previously reported a similar case of NHL from Ugandan pediatric patient [27].…”
Section: Discussionmentioning
confidence: 99%
“…As in our case, no additional therapy was done after the lymphadenectomy in 2 cases, with a favorable course after 2 and 7 years, respectively [ 1 , 4 ]. This attitude raises questions about the accurate benefit of an adjuvant treatment in the management of this entity.…”
Section: Discussionmentioning
confidence: 97%
“…The causal relationship between HHV8 and lymphoproliferative disorder is not yet clearly elucidated [ 5 ]. According to some authors, HHV8+ lymphoproliferation may originate from B-cells at different stages of differentiation [ 4 , 5 , 7 , 9 , 10 ]. Moreover, it was suggested that the maturation stage of HHV8+ B-cells and the type of viral infection (latent or lytic) might define the pathological features of the lymphoproliferation [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous factors must be kept in mind 6 : diabetes, vascular diseases, autoimmune diseases, and other conditions can impair healing up to amputation 1 . The regenerative property of the fat was discovered several years ago: Rigotti already in 2007 understood that lipofilling improved scars in patients undergoing to radiation therapy 7 . It was thought that this effect was mediated by stem cells derived from fat 8 .…”
Section: Discussionmentioning
confidence: 99%